Primary amyloidoma of chest wall – a rare condition - Kumar, Suresh (BMJ Publishing Group, 2012)
Organ specific amyloidosis has been shown to be confined to various organs like liver, lung, spleen, urinary bladder and gastro-intestinal tract, but amyloidoma or tumoural amyloidosis of chest wall with no evidence of systemic amyloidosis is an extremely rare presentation and only two cases have been reported till now. The authors report a case of chest wall amyloidoma with review of literature.